Le “Aule Verdi” per Educare all’Ambiente e Intercultura: Uno Studio di Caso - Calvano, Gabriella (European Journal of Sustainable Development, 2014)
Environment is not only the ensemble of elements that is present in a context, but it is also the ensemble of relationships between these elements. For this reason, in the complexity’s society, educate to environment entails to pay attention to people, to relationships and to dialogue opportunities among them. This case study underlines intercultural dialogue opportunities that could be created by an educational path of environmental education in a Primary School. This experimental research has lead to the construction of a Mediterranean Garden in outward space of school. Through education to environment and biodiversity it is possible to put foundations for dialogue between different cultures, as different are biological species that form Mediterranean Garden. Keywords: educazione ambientale, educazione interculturale, aula verde, laboratorio, biodiversità